An efficient textile-based electrode utilizing silver nanoparticles/reduced graphene oxide/cotton fabric composite for high-performance wearable supercapacitors. (1st February 2021) - Karami, Zahra; Youssefi, Mostafa; Raeissi, Keyvan; Zhiani, Mohammad
Abstract: An efficient textile-based electrode was successfully prepared by introducing silver nanoparticles (AgNPs) on the surface of reduced graphene oxide (RGO) coated cotton fabric (CF) using a simple, cost-effective, room-temperature, rapid, and scalable electroless plating method. The Ag/RGO coated CF showed a high specific capacitance of 426±10 F/g in 0.5 M NaOH electrolyte during the CV cycles. Symmetric supercapacitor cells based on Ag/RGO/CF composite possessed outstanding cycle life (126% retention of initial specific capacitance after 1000 charge-discharge cycles) and good rate capability. The coating layer of RGO endows the electrode an excellent electrical conductivity, high surface area, and good electrical double-layer capacitance. Simultaneously, the electroless plating of silver improves the capacitive behavior due to an increase of conductivity and induce the pseudocapacitive effects. Hence, beneficial synergistic effects of RGO, AgNPs, and 3D hierarchical structure of CF lead to an excellent energy storage performance. The all-solid-state flexible symmetric supercapacitor was assembled using this composite textile, which exhibited high electrochemical performance stability under mechanical bending (89% of initial capacitance retained after 1000 bending cycles) and delivered energy density as high as 34.6 Wh kg −1 (at a power density of 125 W kg −1 ). Therefore, this novel and high-performance electrode is a promising candidate for the next-generation wearable supercapacitors.